2002
DOI: 10.1021/jp020242g
|View full text |Cite
|
Sign up to set email alerts
|

Ions at the Air/Water Interface

Abstract: We present results from theoretical studies of aqueous ionic solvation of alkali halides aimed at developing a microscopic description of structure and dynamics at the interface between air and salt solutions. The traditional view has depicted the air/solution interface of simple electrolytes as being devoid of ions. However, it is now firmly established that polarizable anions, such as the heavier halides, occupy the surface of small to medium sized water clusters. Using a combination of theoretical calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

95
920
10
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 760 publications
(1,032 citation statements)
references
References 110 publications
(327 reference statements)
95
920
10
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] These findings contradict the textbook description of ions being repelled from the interface and the outermost surface layer being devoid of ions. [10][11][12] This conventional wisdom is largely based on macroscopic measurements of the increasing surface tension of aqueous solutions with salt concentration.…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] These findings contradict the textbook description of ions being repelled from the interface and the outermost surface layer being devoid of ions. [10][11][12] This conventional wisdom is largely based on macroscopic measurements of the increasing surface tension of aqueous solutions with salt concentration.…”
Section: Introductioncontrasting
confidence: 65%
“…The ions and molecules were placed in a simulation box with dimensions 30 × 30 × 150 Å 3 and periodic boundary conditions were employed. Due to the elongated z-length of the box an infinite liquid slab was formed in the middle of the z-dimension with two planar liquid-vapor interfaces.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The atom positions for each cluster considered were obtained from a MD simulation of 1.2 M NaCl in water at 300 K, where polarization of both the solvent and the solvated ions are explicitly included. 34 As with H 3 O + , only configurations containing one cation and no anions were considered in order to simplify the interpretation of the calculated spectra. Additionally, XA spectra of the central water molecule in 17 molecule pure water clusters, taken from an MD simulation of pure water, 34 and in 17 water molecule/1 Cl -clusters, taken from the 1.2 M NaCl simulation, were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, a combination of computational [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimental studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] has shown that ions can reside and even be enhanced at the interface.…”
Section: Introductionmentioning
confidence: 99%